Factors influencing the adoption of responsibility accounting in the digital transformation context of Vietnamese enterprises - Thu, Pham Thi (Edelweiss Applied Science and Technology, 2025)
In the context of rapid digital transformation, the adoption of Responsibility Accounting (RA) has become essential for enhancing managerial control and accountability within enterprises. This study investigates the factors influencing the extent of RA adoption in Vietnamese enterprises, focusing on six key determinants: management accounting competency (MAC), accounting information system quality (AISQ), digital transformation capability (DTC), degree of decentralization (DE), innovation culture (IC), and competitive pressure (CP). Data were collected from 400 enterprises through a structured survey and analyzed using quantitative techniques, including Cronbach’s Alpha, Exploratory Factor Analysis (EFA), and multiple regression analysis. The results indicate that all six factors exert positive and statistically significant effects on RA adoption, with digital transformation capability, accounting information system quality, and management accounting competency being the strongest predictors. The study concludes that RA implementation is jointly shaped by technological capabilities, information quality, and organizational characteristics. These findings provide important managerial implications for enterprises in improving information systems, accelerating digital transformation, and enhancing internal control mechanisms to strengthen managerial effectiveness in the digital era.